You and Your Baby: A national survey of health and care during the 2020 Covid-19 pandemic - Harrison, S; Alderdice, F; McLeish, J; Quigley, MA (National Perinatal Epidemiology Unit, University of Oxford, 2021)
You and Your Baby 2020 explored the health and experiences of maternity care for women who gave birth during the first wave of the Covid-19 pandemic. The study included a survey of 4,611 women recruited through the register of all births in England (the 2020 National Maternity Survey (NMS)). The women in the 2020 NMS gave birth in England during May 2020. The study also included a parallel survey of 1,622 women recruited through social media. The women in the social media survey gave birth in the UK between March and August 2020. The findings indicate that some aspects of women's health and maternity care remained consistent or even improved during Covid-19, compared with findings from before the pandemic. Overall levels of satisfaction with care during pregnancy and birth remained high. The findings also indicate, however, that other aspects of women's health and care were negatively impacted by Covid-19, particularly after giving birth. Overall levels of satisfaction with care during the postnatal period fell considerably compared with findings from before the pandemic. Taken together the survey findings suggest that giving birth during the COVID-19 pandemic may have brought additional stresses for women and families at what can already be a challenging time. Covid-19 may have introduced new challenges to maternity services and also amplified some of the existing problems in parts of the system.